Going, Going, Gone: Cush in the Crosshairs - Corbett, Glenn J. (The Biblical archaeology review, 2025)
Often overshadowed by the grandeur of ancient Egypt, the land of Cush in modern-day northern Sudan was no less impressive in its cultural achievements. From at least the third millennium BCE, the Cushites grew wealthy and powerful from the region’s rich mineral deposits, especially gold, as well as their control over strategic trade routes that […]